Comparison Of Parenteral Iron Sucrose And Oral Iron Therapy In Managing Iron Deficiency Anemia In The Post-Partum Period - Aslam, Rakhshanda; Kouser, Maimoona; Aziz, Moizza; Asma, Addiba Sultan; Fatima, Ambreen; Nadeem, Ammarah (Journal of Rawalpindi Medical College, 2025)
OBJECTIVE The goal of this study is to assess the effectiveness of parenteral iron sucrose therapy vs oral iron supplements in the treatment of iron deficiency anaemia (IDA) in the postpartum period. METHODOLOGY: This study is conducted in the OBS and Gynae department of PAF Hospital Islamabad. This is a randomized control trial (RCT). A total of 130 women, 65 in each group were recruited who were diagnosed with iron deficiency anaemia (as per operational definition ), 48hrs after delivery. In group A females were prescribed intravenous iron sucrose therapy according to post-delivery hemoglobin level by using the formula (2.4 × (target Hb-actual Hb) × post-pregnancy weight (kg)) + 1000 mg every alternate day. In group B females were prescribed daily oral iron supplements along with folic acid. Follow-up of both groups was done after 4 weeks in OPD. RESULTS: The mean age was 29 years ± 2.688 in group A, while in group B it was 30 years with SD ±2.422. In group A (Intravenous iron sucrose therapy) mean ferritin level was 140.94 ± 3.292 and the mean hemoglobin level was 11.11 ± 0.710. In group B (Oral iron supplements) mean serum ferritin level was 125.34 ± 6.551 and the mean Hemoglobin level was 10.65 ± 0.623 after treatment. CONCLUSION Our study concludes that there is no significant difference in treatment between intravenous iron sucrose therapy and oral iron supplements for iron deficiency anaemia in the post-partum period.